Critical Discourse Analysis of Teun A. Van Dijk Model on Rob Sixmith's Ice Cold Murder Coffee and Jessica Wongso (2023) Movie - Nayuda Septa Haidar; Rizzca Haqqu (CV. Publikasi Indonesia, 2024)
This research is based on the cyanide coffee case involving Jessica Wongso. The case became a hot topic of conversation in Indonesia and attracted widespread attention due to its complexity and intense media attention. The popularity and controversy of this case resurfaced because Netflix made a documentary titled Ice Cold: Murder, Coffee and Jessica Wongso, which explains the debates related to the verdict of Jessica, who was considered a convict with several irregularities. The presence of the film led to various assumptions from experts and the public, so there was social criticism related to the justice system in the Jessica Wongso case. This sparked the interest of researchers in conducting this research. To support this research, the theory considered appropriate to analyze this documentary is Teun A Van Dijk's critical discourse analysis. Critical discourse analysis describes how discussions or discourses about an event influence and affect existing social institutions and structures. To obtain field data, researchers feel it is appropriate to use qualitative research with a critical paradigm that analyzes text structure, social cognition, and social context. The results showed that there is a discourse of social criticism in the documentary film